I am assuming that you actually mean "axis of symmetry"
Note. For a quadratic function in the Vertex Form: f(x) = a(x - h)^2 + k
The equation for the axis of symmetry is x = h
The quadratic function f(x) = (x + 2)^2 - 4 is in vertex form. Meaning we can compare with f(x) = a(x - h)^2 + k to get our value of 'h'. Then we can use this value to obtain your equation for the function's axis of symmetry.
f(x) = (x + 2)^2 - 4 <Given quadratic function. It is in vertex form>
f(x) = a(x - h)^2 + k <Compare give quadratic function with the vertex form>
x + 2 = x - h <We would compare the expressions in parenthesis>
x + 2 - x = x - h - x <Subtract both sides by x>
2 = -h
-2 = h <Negate both sides>
h = -2
Now that we have our value of h, we can obtain our equation for the axis of symmetry
x = h <Equation for the axis of symmetry>
x = -2 <Substitute the value of h>
SOLUTION: Equation for the axis of symmetry is x = -2
Content will be erased after question is completed.